Methods, models, and computation for medical informatics - Gangopadhyay, Aryya 1962- (Medical Information Science Reference, 2013)
"This book is a comprehensive collection of research on the computational capabilities, prototypes and algorithms and their application to the areas of nursing, clinical care, public health, biomedical research and much more" - Provided by publisher
Includes bibliographical references and index
Keywords: Aufsatzsammlung